Correction to: Safety and Efficacy of 0.5% Carbomer 980 Gel for Treatment of Symptoms of Common Cold: Results of 2 Randomized Trials - Lara Dennie; Gilbert Shanga (Adis, Springer Healthcare, 2019)
The original publication of the article contained the following errors.